The design of two apparati to measure solid-liquid and liquid-liquid equilibria data. - Tadie, Margreth. (2011)
Two new apparati have been developed to measure solid-liquid and liquid-liquid equilibria via a synthetic visual method by determination of thermal signatures. One apparatus adopts a technique of using Peltier modules for cooling, and the other is a well-known design that uses a cryogenic fluid in a thermostatted glass cell for cooling of the sample. The Peltier design is for small sample volumes, with a 10 cm3 aluminium equilibrium cell and has a minimum operating temperature of 253.15 K. The glass design is developed to complement the Peltier and has a larger volume of 140 cm3 and a minimum operating temperature of 223.15 K. Both apparati have been semi-automated in order to increase the accuracy and improve the efficiency of data measurements. Therefore the experimenter no longer has to wait for many hours for the determination of equilibrium. This was done by incorporating software, which was specially designed for the apparati using Labview8TM, for controlling the cooling and heating rates. The uncertainty of the temperature measurements was found to be ±0.03 K for the Peltier apparatus and ±0.02 K for the Glass apparatus. Liquid-liquid equilibria data has also been measured on the Peltier apparatus, to demonstrate its versatility. This was done using a digital camera, controlled through the Labview software to identify cloud points. The results have been found to be comparable with literature values.